Penyelenggaraan Pemerintahan Daerah dalam Urusan Konkuren Bidang Pelayanan Dasar di Kota Serang - Rizki Ramadhan Faisal; Aidul Fitriciada Azhari (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to identify and describe problems regarding the implementation of local government in concurrent affairs of the basic services in Serang. Basic services based on Law Number 23 of 2014, include: a. education; b. Health; and c. Social. This article formulates the following problems: 1. What are the problems in Serang?, 2. What factors that influence the implementation of local government in education, health, and social affairs in Serang?. The author identifies four main problems: a. The condition and availability of regional infrastructure is not optimal; b. lack of innovation and low competitiveness of the regional economy; c. The implementation of governance is not yet optimal; and d. The implementation of local government in education, health and social affairs is not yet optimal. This research uses analytical descriptive research. Based on the four problems mentioned earlier, the local government should immediately design and reorganize priority scale programs in the Regional Development Work Plan (RKPD). It is hoped that it will have good impact toward the community and the implementation of local government based on the principles of good governance.